Work Motivation and Work Discipline on the Performance of Educators - Susi Yuliastanty; Stepanina Stepanina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2023)
The aim of the study was to determine the influence of work motivation and work discipline on the performance of teaching staff at SMA Negeri 1 South Siberut , Mentawai Regency. Data collection methods are Field Research and Library Research. Types and sources of data are primary data and secondary data. The population of this study were all teaching staff at State Senior High School 1 Siberut Selatan, Mentawai Regency, both with PNS status and a sample of 37 people. The analytical method uses multiple linear regression analysis. The results of the study are: (1) Work motivation partially has a significant effect on the performance of civil servant educators at SMA Negeri 1 Siberut Selatan, Mentawai Regency. (2) Work discipline partially has a significant effect on the performance of civil servant educators at SMA Negeri 1 Siberut Selatan, Mentawai Regency. (3) Work motivation and work discipline have a significant effect on the performance of civil servant educators at SMA Negeri 1 Siberut Selatan, Mentawai Regency.